PENERAPAN LOGIKA FUZZY MENGGUNAKAN METODE MAMDANI DALAM OPTIMASI PERMINTAAN OBAT - Inggrid Raga Djara; Tiwuk Widiastuti; Dony M Sihotang (Universitas Nusa Cendana, 2019)
Planning a good drug supply at the puskesmas is needed to support health services provided by the puskesmas, in addressing the problem of planning drug requests to suit the needs that exist, the researcher uses Mamdani method in fuzzy form that are making fuzzy set, application of rule function, composition rule, affirmation (defuzzy) using method of MOM (Mean of Maximum). Parameters used are initial stock, receipt, preparation, use, ending and demand stock. The calculation was performed using data for 2 years, and it was done 1 year to compare the results of the Health Centre request and the system request. From the test results, the total system demand is smaller than the total demand for Puskesmas, so the system optimization is obtained at 7.623% for 3 drug data so that it can increase the efficiency of the budget funds of Rp. 3,168,223, so it can be concluded that the Fuzzy Mamdani method is a method that provides optimal solutions